Can artificial ıntelligence detect the anti-aging effect of rhinoplasty? - Muhammed Zeki Yalçın; Yuksel Toplu; Osman Kurt (Journal of Plastic Surgery and Hand Surgery)
Background: The quest for eternal youth has been a common theme in many cultures for centuries. While we have yet to discover a way to preserve youth eternally, we have made significant progress in understanding the aging process and in developing pharmaceuticals, surgical techniques, and technologies.